Comparisonal Analysis of Compensation Using Adhered Method and Overlapping Method - Adela Fortunada; Salsabila Putri R; Muhammad Akbar Ajiatmojo; Mohamad Rifki Aufan; Moh. Naufal Wafiq A (Ridwan Institute, 2021)
Compensation is an important factor for workers to foster a sense of enthusiasm and self-motivation in working to achieve company goals. On the other hand, the company must also understand the position and role of workers in it so that in determining the amount of compensation it can be determined in a balanced manner and minimize operational expenses that are too large. Both financial compensation and non-financial compensation, the company has an obligation to fulfill both of these things, so that the standard of living needs of workers can be met properly. The object of this research is PT Diva Jaya Trans, which is located in the city of Demak, Central Java. This company is engaged in the tourism transportation sector with a total of 7 bus fleets, and a total of 22 workers, and occupying various positions, such as admin, marketing, foreman, and crew. The research methods used are quantitative and qualitative sourced from trusted scientific journals and articles. This research focuses on the compensation sector and KHL. In this case, we identify and make improvements to the compensation system, namely by using the adhered method and the overlapping method. To determine the effectiveness of the two methods, salary data that has been obtained from the director through direct and online interviews was processed so that several gaps were found from the adhered method and the overlapping method. The final result of this study shows that the overlapping method is feasible to be considered for compensation changes in the company object, because according to the calculation it has a fairly good ratio